Pre- and Post-natal Development of Skin Characteristics in the One-humped Camel (Camelus dromedarius) - M. Marai, I Fayez; Khalil, Agned B A (Annals of Arid Zone, 2016)
In a studied camel the epidermis began to appear as a single row of cells in 90 days, and both epidermis and dermis were fully developed in 147 days of foetal life when the epidermis was differentiated into its four strata (corneum. granulosum. spinosum and basale or germinativum). The dermis was differentiated into papillary and reticular sub-layers. The plugs which would form the hair follicle began to appear in 147 days, while the hair fibres began to appear in its follicles in 268 days of foetal life. The follicles were clearly differentiated into primary and secondary follicles at 286 days of foetal life. The hair follicles were arranged in groups and were clearly seen at 275 days of foetal life. Each group consisted of three primary. follicles and several secondary follicles. The thickest secondary follicles (ear secondary follicles) were situated near the primaries, while the thinner secondaries (late secondary follicles) were found far from the primary follicles). The thickest secondary follicles (early secondary follicles) were situated near the primaries, while the thinner secondaries (late secondary follicles) were found far from the primaries. The primary follicle was associated with a sebaceous gland, a sweat gland and an arrector pili muscle, while each secondary follicle was associated only with a sebaceous gland. The sebaceous glands that were attached to the primary follicles had large lobules, while those attached to the secondaries were smaller. Several lobules of the sebaceous glands opened into a common short excretory duct. The sebaceous glands began to appear at 229 days of foetal life. The apocrine sweat gland was formed of a glandular tortuous part and its uppermost straight duct passed between or beside the sebaceous gland lobules, then enlarged in a sac before it opened near the follicle opening at the skin surface. The tortuous glandular distal part was situated either at or lower than the level of the hair follicle bulb and was formed of one layer of cuboidal epithelium. The sweat glands began to appear at 147 days of foetal life. The arrector pili muscle was formed of smooth muscle fibres. It ran from the lower part of the follicle to the area below the epidermis. The arrector pili muscles first appeared at 229 days of foetal life ..